2008
DOI: 10.1111/j.1463-1326.2008.00915.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of insulin analogue regimens in people with type 2 diabetes mellitus in the PREFER Study: a randomized controlled trial

Abstract: Modern insulin analogue regimens, adjusted to PG targets, enable a majority of people with T2DM to reach HbA(1c)< or =7.0% after failure of OADs and OAD-basal insulin therapy. Insulin-treated patients may benefit more from transfer to analogue basal-bolus therapy, while insulin-naive individuals benefit equally well from the more convenient biphasic analogue regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
134
3
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(151 citation statements)
references
References 21 publications
10
134
3
4
Order By: Relevance
“…Although it is always necessary to exercise care when adjusting the insulin dose, and to pay attention to possible interactions with coadministered drugs, the characteristics of BIAsp 30 suggest that it may be possible to increase the dose slightly, and reduce HbA1c levels further without increasing the incidence of hypoglycemic episodes. Since several previous studies [13][14][15][16][17][18] , some of them were conducted in Japanese patients, have shown that BIAsp 30 improved HbA1c/daily glycemic profiles equally versus multiple insulin injection therapy or better than previous OAD therapy in insulinnaïve patients. Hypoglycemic episodes were not increased versus these regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is always necessary to exercise care when adjusting the insulin dose, and to pay attention to possible interactions with coadministered drugs, the characteristics of BIAsp 30 suggest that it may be possible to increase the dose slightly, and reduce HbA1c levels further without increasing the incidence of hypoglycemic episodes. Since several previous studies [13][14][15][16][17][18] , some of them were conducted in Japanese patients, have shown that BIAsp 30 improved HbA1c/daily glycemic profiles equally versus multiple insulin injection therapy or better than previous OAD therapy in insulinnaïve patients. Hypoglycemic episodes were not increased versus these regimens.…”
Section: Discussionmentioning
confidence: 99%
“…26 Basal-bolus insulin therapy was compared with biphasic premixed insulin therapy in patients who failed on oral hypoglycaemic agents or who failed on oral hypoglycaemic agents combined with basal insulin therapy. 27 There was no difference between the two regimens in terms of HbA1c reduction, fasting and postprandial glucose reduction, weight gain and hypoglycaemic events. 27 The problem is that biphasic premixed insulin therapy is not physiological and the doses of intermediate-acting insulin and short-acting insulin are not flexible.…”
Section: Insulin Strategiesmentioning
confidence: 99%
“…27 There was no difference between the two regimens in terms of HbA1c reduction, fasting and postprandial glucose reduction, weight gain and hypoglycaemic events. 27 The problem is that biphasic premixed insulin therapy is not physiological and the doses of intermediate-acting insulin and short-acting insulin are not flexible. 28 The one dose of biphasic premixed insulin cannot be adjusted without affecting the other dose.…”
Section: Insulin Strategiesmentioning
confidence: 99%
“…This allows us to examine the studies according to patient population: studies of insulin-naive patients initiating insulin with BIAsp 30, [35][36][37][38][39][40][41][42][43][44][45][46][47][48] and studies of patients switching existing insulin therapy to, or intensifying with, BIAsp 30.…”
Section: Type 2 Diabetesmentioning
confidence: 99%